2019
DOI: 10.1007/s10198-019-01126-2
|View full text |Cite
|
Sign up to set email alerts
|

How averse are the UK general public to inequalities in health between socioeconomic groups? A systematic review

Abstract: There is growing interest in the use of "distributionally-sensitive" forms of economic evaluation that capture both the impact of an intervention upon average population health and the distribution of that health amongst the population. This review aims to inform the conduct of distributionally sensitive evaluations in the UK by answering three questions: (1) How averse are the UK public towards inequalities in lifetime health between socioeconomic groups? (2) Does this aversion differ depending upon the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…NICE’s commitment to addressing inequalities is illustrated by the fact that it considered adding impact on inequalities as a modifier to future health technology appraisals [ 4 ]. This is based on equality legislation [ 37 ] and evidence suggesting that the UK population prioritises seeking a fair distribution of health across society and is willing to trade-off less health overall if the health is generated in disadvantaged groups, particularly for socioeconomic disadvantage [ 38 ]. However, further work is needed to explore which sources of inequality to include, whether direct and indirect effects would be considered, and how and in which circumstances this could be implemented in health technology evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…NICE’s commitment to addressing inequalities is illustrated by the fact that it considered adding impact on inequalities as a modifier to future health technology appraisals [ 4 ]. This is based on equality legislation [ 37 ] and evidence suggesting that the UK population prioritises seeking a fair distribution of health across society and is willing to trade-off less health overall if the health is generated in disadvantaged groups, particularly for socioeconomic disadvantage [ 38 ]. However, further work is needed to explore which sources of inequality to include, whether direct and indirect effects would be considered, and how and in which circumstances this could be implemented in health technology evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have elicited public values for non-health policies and their associated (non-)health outcomes. Stated preference research exists on the public's aversion to inequalities in health between socioeconomic groups (McNamara et al, 2020) and there are valuation studies of public health interventions such as water fluoridation and salt reduction (Kristiansen et al, 2006;Shackley and Dixon, 2000). There is also a large stated preference literature on nonhealth policies with non-health outcomes, for example, in environmental and transport sectors (Bahamonde-Birke et al, 2015;Carson and Hanemann, 2005) and there are public attitude/opinion surveys on redistributive non-health policies (for example, Reid et al (2019)).…”
Section: Why Should Public Values Be Elicited For Tackling Health Inequalities?mentioning
confidence: 99%
“…A systematic review found significant aversion amongst the UK public to health inequalities, particularly when such inequalities are presented in the context of socioeconomic differences (43). Thus, any suggestion that the use of AI in medicine may exacerbate existing health inequalities, for example by automating existing bias and unfairness at speed and scale, is likely to decrease trust in and acceptability of these tools.…”
Section: Health Inequalitiesmentioning
confidence: 99%